Profitability and working capital management: evidence from the Warsaw Stock Exchange - Jaworski, Jacek; Czerwonka, Leszek (Journal of Business Economics and Management, 2022)
The aim of this paper is to identify the relationships between measures of working capital management (cash conversion cycle /CCC/, working capital value /WC/ and the financial liquidity /CR/) and profitability of companies listed on the Warsaw Stock Exchange. The research material consisted of data of 326 companies from 1998–2016. The analysis revealed significant non-linear relationship between WC, CR and profitability. When WC and CR values grow, profitability increases, but at a slower pace. However, there is a linear negative relationship between CCC and profitability. The results are influenced by the industry and the GDP growth. This indicates that profit-driven entrepreneurs try to delay payments to suppliers. They pay off bank loans from the funds thus generated. This study contributes to the verification of theories linking profitability with working capital management with emphasis on the influence of the industry. The results have practical implications: companies with growing profitability should not lose sight of the shortening CCC when paying off short-term loans; in some industries decreasing profitability while CR values grow may mean problems with the efficient use of current assets.